Üniversite öğrencilerinin demokratik tutumları ile öğrenci kulüplerinin etkililiği arasındaki ilişki - Aytekin, Ali (İstanbul Sabahattin Zaim Üniversitesi, 2022)
Bu araştırmanın amacı, öğrencilerin demokratik tutumları ile üniversite öğrenci kulüplerinin etkililiği arasındaki ilişkinin belirlenmesidir. . İlişkisel tarama modeline göre gerçekleştirilen bu araştırmanın evrenini 2020-2021 eğitim-öğretim yılında, İstanbul Sabahattin Zaim Üniversitesinde 5 fakültede öğrenim görmekte olan 6104 sayıdaki öğrenci oluşturmaktadır. Araştırmanın örneklemini ise evrende yer alan fakültelerden tesadüfi tabakalı örneklem yöntemiyle belirlenen 552 öğrenci oluşturmaktadır. Veriler, araştırmacı tarafından geliştirilen "Demokratik Tutum Ölçeği" ve "Üniversite Kulüpleri Etkililiği Ölçeği" aracılığıyla toplanmıştır. Verilerin analizinde frekans, yüzde, t-test, tek yönlü varyans ve pearson korelasyon analizleri kullanılmıştır. Bulgulara göre öğrencilerin demokratik tutum düzeyleri, cinsiyet, sınıf ve öğrenim gördükleri fakültelere göre anlamlı farklılık göstermektedir. Öğrencilerinin kulüplere yönelik görüşleri, cinsiyet, sınıf ve öğrenim gördükleri fakültelere göre anlamlı farklılık göstermektedir. Üniversite öğrencilerinin demokratik tutum düzeyleri ile üniversite öğrenci kulüplerine ilişkin görüşleri arasında anlamlı bir ilişki görülmemektedir.

The aim of this research is to determine the relationship between the democratic attitudes of students and the effectiveness of university student clubs. The universe of this research, which was carried out according to the relational scanning model, consists of 6104 students studying at 5 faculties at İstanbul Sabahattin Zaim University in the 2020-2021 academic year. In the sample of the study, there are 552 students from the faculties in the universe that were determined by the random stratified sampling method. The data were collected through the "Democratic Attitude Scale" and "University Clubs Effectiveness Scale" that were both developed by the researcher. The frequency, percentage, t-test, one-way variance and Pearson correlation analyses were used in the analysis of the data. According to the findings, the democratic attitude levels of the students differ significantly according to their gender, year of study and their respective faculties. Students' opinions about clubs differ significantly according to gender, year of study and faculties. There is no significant relationship between the democratic attitude levels of university students and their views on university student clubs.
The relationship between the democratic attitudes of university students and the effectiveness of student clubs
Keywords: Demokratik Tutum; Öğrenci Kulüpleri; Etkililik; Democratic Attitude; Student Clubs; Effectiveness